Staging indigeneity salvage tourism and the performance of Native American history - Phillips, Katrina M. (University of North Carolina Press, 2021)
"As tourists increasingly moved across the United States in the late nineteenth and early twentieth centuries, a surprising number of communities looked to capitalize on the histories of Native American people to create tourist attractions. From the Happy Canyon Indian Pageant and Wild West Show in Pendleton, Oregon, to outdoor dramas like 'Tecumseh!' in Chillicothe, Ohio, and 'Unto These Hills' in Cherokee, North Carolina, locals staged performances that claimed to honor an Indigenous past while depicting that past on white settlers' terms. Linking the origins of these performances to their present-day incarnations, this incisive book reveals how they constituted what Katrina Phillips calls 'salvage tourism' - a set of practices paralleling so-called salvage ethnography, which documented the histories, languages, and cultures of Indigenous people while reinforcing a belief that Native American societies were inevitably disappearing"